CogToM-CST: An implementation of the Theory of Mind for the Cognitive Systems Toolkit - Grassiotto, Fabio; Colombini, Esther Luna; Simoes, Alexandre [UNESP]; Gudwin, Ricardo; Paro Costa, Paula Dornhofer; Rocha, A. P.; Steels, L.; VandenHerik, J. (Scitepress, 2022)
This article proposes CogToM-CST, an implementation of a Theory of Mind (ToM) model using the Cognitive Systems Toolkit (CST). Psychological research establishes that ToM deficits are usually associated with mind-blindness, the inability to attribute mental states to others, a typical trait of autism. This cognitive divergence prevents the proper interpretation of other individuals' intentions and beliefs in a given scenario, typically resulting in social interaction problems. Inspired by the psychological Theory of Mind model proposed by Baron-Cohen, this paper presents a computational implementation exploring the usefulness of the common concepts in Robotics, such as Affordances, Positioning, and Intention Detection, to augment the effectiveness of the proposed architecture. We verify the results by evaluating both a canonical False-Belief task and a subset of tasks from the Facebook bAbI dataset.
Keywords: Autism; Cognitive Architectures; Artificial Intelligence